DEVELOPMENT OF LOCAL WISDOM OF TUAK REACTION RATE TEACHING MATERIALS INTEGRATED WITH PROBLEM-BASED LEARNING - Br Singarimbun, Veronica Liasta; Silaban, Ramlan (Universitas Samudra, 2025)
This study aims to develop a teaching material in the form of a textbook based on the local wisdom of tuak, integrated with the Problem-Based Learning (PBL) model, for the topic of reaction rates in Grade XI MIA-2 at SMA Methodist-An Pancur Batu. The development model used in this study is the 4D model. The 4D model (Define, Design, Develop, Disseminate) is a systematic approach commonly used in instructional development to produce high-quality learning products. Based on the analysis, it was found that SMA Methodist-An Pancur Batu has implemented the Independent Curriculum (Kurikulum Merdeka) at Phase F, but has not yet incorporated local wisdom into the learning process. Moreover, the textbooks previously used did not apply the PBL approach. In this study, a reaction rate textbook based on the local wisdom of tuak was developed in accordance with the Independent Curriculum, including Learning Outcomes (CP), Learning Objective Flow (ATP), and strengthening the Pancasila Student Profile. Validation results showed that the material expert's assessment obtained an average score of 3.83, while the media expert's score was 3.68—both categorized as valid and requiring no revision. Teacher responses to the developed textbook reached 95% (very good), while student responses were 93.3% (very good). Thus, this textbook is considered feasible and effective for use as a learning resource that incorporates local wisdom and is integrated with the Problem-Based Learning model in chemistry education at school